HUBUNGAN PERSEPSI ORANG TUA TENTANG KENAKALAN REMAJA DENGAN PENATALAKSANAAN TUMBUH KEMBANG REMAJA DI DESA ADIKARTO KECAMATAN ADIMULYO KABUPATEN KEBUMEN - Retnowati, Eko; -, Marsito; Yuwono, Podo (LPPM STIKES MUHAMMADIYAH GOMBONG, 2014)
Adolescence is a period of life that is full of dynamics, which occurs during development and change very rapidly and lasts between 11 to 20 years of age. This period of transition from childhood to adulthood. Growth and development in adolescents can not be separated from a parents attention. Parents are responsible and important role in the management of adolescent growth and development better. The purpose of this study was to determine the relationship between perception parents about the treatment of juvenile delinquency with adolescent growth and development in the Village Adikarto, District Adimulyo, Kebumen. This research uses descriptive method with approach of cross sectional correlation. Data analysis using the Kendall Tau correlation test to determine the relationship between variables. Sample of 33 respondents in the study inclusion and exclusion criteria.There is a significant relationship between parents perception about the management of juvenile delinquency with adolescent growth and development in the Village Adikarto, District Adimulyo, Kebumen indicated by the value of t calculated 0.284 (p = 0.028). There is a significant relationship between parents perception about the management of juvenile delinquency with adolescent growth and development in the Village Adikarto, District Adimulyo, Kebumen. Â Keywords: Parents, Juvenile Delinquency, Growth and Development